Lipid-enriched reduced nutrient culture medium improves bovine blastocyst formation - Rolando Pasquariello; Mingxiang Zhang; Jason R Herrick; Alison F Ermisch; John Becker; William B Schoolcraft; Jennifer P Barfield; Ye Yuan; Rebeca L Krisher (Bioscientifica, 2023)
The refinement of embryo culture media is essential in improving embryo viability and in vitro production efficiency. Our previous work demonstrated that the nutrients (carbohydrates, amino acids, and vitamins) in traditional culture media far exceed the need for an embryo and producing developmentally competent embryos in a reduced nutrient environment is feasible. Here, we aim to evaluate the impact of exogenous lipid and l-carnitine supplementation on bovine blastocyst development and refine our RN condition further. Zygotes were cultured in the control medium (100% nutrients) and reduced nutrient media containing 6.25% of the standard nutrient concentrations supplemented with l-carnitine and lipid-free or lipid-rich BSA. Increased blastocyst development was observed in the reduced nutrient lipid-rich medium compared to the other two groups. However, in both reduced nutrient conditions, blastocyst cell numbers were lower than those obtained in the control condition. We then examined the expression level of 18 transcripts correlated with lipid metabolism, glucose metabolism, redox balance, and embryo quality, along with mitochondrial DNA copy numbers, ATP productions, and lipid profile. The results indicated that lipid metabolism, embryo quality, and redox enzyme-related genes were upregulated while the glucose-related gene was downregulated in embryos derived from reduced nutrient lipid-rich condition. Finally, we identified that the lipid-rich BSA has enriched linoleic, stearic, oleic, palmitic, and alpha-linoleic fatty acids, a lipid profile that may contribute to the increased lipid metabolism and improved blastocyst development of the bovine embryos under the reduced nutrient condition.